Effect of Energy Tax Reduction on Fuel Prices - Volker Brühl (Wirtschaftsdienst)
Abstract The German federal government intended to alleviate the burden of increasing fuel prices by introducing a temporary reduction of energy taxes on gasoline and diesel. In order to evaluate the impact of this measure on consumer prices at the filling stations the development of procurement costs for crude oil as well as the downstream development of refinery and distribution margins have to be taken into account. It turns out that about 80 % of the tax reduction has been passed on to end consumers on and around the effective date of the tax relief. However, within the first month the impact of the tax reduction has been wiped out for diesel completely as the gross margin of the mineral oil groups have substantially improved since then. On the other hand, for gasoline (E10) at least part of the impact can still be observed as the initial margin improvement has come down in the meantime. For a detailed analysis the German antitrust authority should look into the pricing algorithms of all 14,000 filling stations in Germany.